S24 Differentiated primary bronchial epithelial cell (pBECs), monocyte derived macrophages (MdMs) and monocyte derived dendritic cells (MODCs) transwell co-culture: Respiratory Syncytial Virus (RSV) infection of the apical and basolateral surfaces. (16th November 2010) - Ugonna, K B; Plant, K; Everard, M L
Abstract : Introduction and Objectives: RSV causes winter epidemics of respiratory disease. Active infection is virtually absent in summer months. Infected ciliated airway epithelial cells, local macrophages and dendritic cells secrete cytokines including interleukins (IL) 6 and 8, promoting a strong neutrophilic response that is important in disease clearance and airway inflammation. In vitro, RSV is capable of infecting MoDCs. RSV inhibits their maturation and can remain dormant in these cells. Dormant RSV can be stimulated to replicate with exogenous nitric oxide. These MoDCs are then able to re-infect HeLa cells (a lab strain of immortalised cervical cells). The following hypothesis was explored: Infected dendritic cells act as a reservoir for RSV over summer months . Aim: The aim of this study was to investigate the effect of RSV on pBEC and MoDc cell lines across a semi permeable membrane in the presence of MdMs. Methods: Primary bronchial epithelial cells were seeded in the apical part of the transwell model at 1×10 6 cells per ml and differentiated over 21 days on an air liquid interface. MoDCs were seeded on the basolateral part of the transwells at 1×10 6 cells/ml. MdM were seeded on top of the epithelial layer in selected experiments (see Abstract S24 Figure 1 ). Red fluorescent RSV (rr-RSV) was added to the apical side at a concentration of 1×10 6 plaque forming units (pfu)/ml with un-infected MoDCs on the basolateral side, and uninfected pBECs in the apical side were co-cultured with MoDCs previously infected with rr-RSV at 5 × 10 5 pfu/ml. Controls were uninfected pBECs with uninfected MoDCs or with just media on basolateral side. Red fluorescence (marker for active infection) was measured at 24, 48 and 168 h by flow cytometry. Results: Directly exposed pBECs and MoDCs were infected at 24 h. Indirectly exposed pBECs were infected at 48 h. Indirectly exposed MoDCs were infected only when MdMs were present on the overlying epithelial cell layer. Conclusions: RSV is able to infect MoDCs and pBEC across a semi-permeable membrane in our in vitro model of airway epithelium, supporting MoDCs as a potential summer reservoir of RSV.